FRI0054 Left Ventricular Function and Structure in Patients with Rheumatoid Arthritis without Cardiac Symptoms: Comparison between Nonbiologic and Biologic DMARD Treatment Groups. (10th June 2014) - Kobayashi, H.; Kobayashi, Y.; Yokoe, I.; Inomata, H.; Ikumi, N.; Kitamura, N.; Shiraiwa, H.; Nozaki, T.; Takei, M.
Abstract : Background: Congestive heart failure (CHF) is a major contributor to morbidity and mortality in rheumatoid arthritis (RA) patients, but effects of disease-modifying antirheumatic drugs (DMARDs) on myocardial structure and function are uncertain. In the general population, cardiac magnetic resonance imaging (CMR) has been used to identify early functional and structural changes in the left ventricle (LV) before development of clinically overt CHF. Objectives: We sought to assess (LV) function and structure using CMR in RA patients without cardiac symptoms to determine the impact of nonbiologic and biologic DMARDs on LV function and structure. Methods: Subjects included 84 consecutive RA patients and 20 controls, all without cardiac symptoms. RA patients received biologic or nonbiologic DMARDs (nbDMARDs). All subjects underwent evaluation of LV function and structure using non-contrast CMR. LV function was measured by LV ejection fraction (EF), end-systolic volume (ESV), end-diastolic volume (EDV), stroke volume (SV), and cardiac output (CO). LV hypertrophy was measured by absolute LV mass (LVM) and LV mass index (LVMI) determined by LVM/BSA. Subjects were classified into 4 categories based on the LVMI and LVM/EDV of control subjects, with the mean + 2 SD of each measure defined as elevated LVMI and LVM/EDV. Results: We compared 84 female RA patients (mean age, 55.8±8.1 years) with a matched 20-patient control group (mean age, 52.7±4.6 years). A total of 43 and 41 of RA patients received nbDMARDs (40, methotrexate (MTX) (8.1±2.1 mg); 3, other drugs) and biologic DMARDs (17, infliximab (3 mg/kg); 24, tocilizumab (8 mg/kg) plus MTX (8.0±1.4 mg), respectively. Among the RA groups, there were no significant differences in characteristics such as age, sex, cardiovascular risk factors, RA duration, MTX dose, and proportion of corticosteroid users. The Disease Activity Score in 28 joints (DAS28) was significantly higher in the nbDMARD group than in the biologic group (4.6±1.10 vs. 2.4±1.1, p =0.002). Compared to the control group, the nbDMARD group showed significantly higher LVMI and significantly lower EF ( p <0.001, p =0.003, respectively). There were no significant differences in LVMI and EF between the control and biologic groups. LV structure was classified as (1) concentric remodeling (LVMI <66.9 and LVM/EDV >1.16); (2) concentric hypertrophy (LVMI >66.9 and LVM/EDV >1.16); (3) eccentric hypertrophy (LVMI >66.9 and LVM/EDV <1.16); and (4) normal geometry (LVMI <66.9 and LVM/EDV <1.16). Among those with abnormal LV geometry, 30% of RA patients in the nbDMARD group showed eccentric hypertrophy, and 1 patient showed concentric remodeling. All patients in the biologic group showed normal geometry. LVMI and EF were significantly associated with DAS28 (r=0.545, p<0.001; r=0.323, p<0.02, respectively). Adjustment for ESR and CRP did not modify the association of DAS28 with LVMI and EF. Conclusions: Biologics treatment may reduce progression of subclinical LV dysfunction and normalize LV structure in association with the reduction in disease activity. It can be presumed that active RA may be an important contributor to the development of myocardial abnormalities. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1914